Assessment of Research Output of Academic Librarians in Public Universities in South-West, Nigeria - Ademola E. , Olanusi; Madukoma, Ezinwanyi; Babalola, Yemisi T. (Communicate: Journal of Library and Information Science, 2023)
This paper investigated research output of academic librarians in public universities in the South-West of Nigeria. The study was guided by two objectives and two corresponding research questions. A survey research design method was adopted for the study. The total population for the study was two hundred and twenty (220) academic librarians in both federal and state universities in the South-West of Nigeria. Therefore, total enumeration was used since the population was manageable. A questionnaire was the instrument used for data collection. Two hundred and three (203) copies of the questionnaire were returned and used for the analysis. Statistical tools such as frequency counts and percentages, the mean, and the standard deviation were used to analyse the data. The result of the analysis revealed that academic librarians’ research output was moderate in terms of quality and quantity. The result showed that lack of funds and the high cost of publication were the major factors militating against the research output of academic librarians in public universities in South-West Nigeria. Based on the findings, it was recommended that time management culture be imbibed by academic librarians in public universities in South-West Nigeria to have ample time for research activities.